2014
DOI: 10.1177/0023677213516314
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided block of sciatic and femoral nerves: an anatomical study

Abstract: The sheep is a popular animal model for human biomechanical research involving invasive surgery on the hind limb. These painful procedures can only be ethically justified with the application of adequate analgesia protocols. Regional anaesthesia as an adjunct to general anaesthesia may markedly improve well-being of these experimental animals during the postoperative period due to a higher analgesic efficacy when compared with systemic drugs, and may therefore reduce stress and consequently the severity of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The number of studies in large animals and in cattle in particular has also increased. There are studies published describing ultrasound‐guided paravertebral blocks (Kramer and others 2014), brachial plexus blocks (Iwamoto and others 2012) and sciatic and femoral nerve blocks in farm animals (Adami and others 2011, Wagner and others 2011, d'Ovidio and others 2014, Waag and others 2014). However, there is still a lack of case reports or studies describing the use of these techniques in calves in a clinical scenario.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies in large animals and in cattle in particular has also increased. There are studies published describing ultrasound‐guided paravertebral blocks (Kramer and others 2014), brachial plexus blocks (Iwamoto and others 2012) and sciatic and femoral nerve blocks in farm animals (Adami and others 2011, Wagner and others 2011, d'Ovidio and others 2014, Waag and others 2014). However, there is still a lack of case reports or studies describing the use of these techniques in calves in a clinical scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human medicine have shown an increased success rate when sonographic guidance was used for the performance of the peripheral nerve blocks [ 42 ]. The study from Waag et al provided a detailed anatomical description of the sciatic and the femoral nerves [ 30 ]. In the present study, only one sheep received rescue analgesia intraoperatively, leading to the assumption that the applied technique was adequate and the success rate was nearly 100%.…”
Section: Discussionmentioning
confidence: 99%
“…With this technique loss of sensation as well as motor function are confined to the operated limb and a combined block of the sciatic and the femoral nerves might lead to profound peri-operative analgesia while standing ability is maintained on three limbs. The most simple technique to apply sciatic–femoral–nerve blocks is the use of anatomical landmarks [ 19 , 30 ]. Nerve stimulators (NS) have been used to improve the success rate of peripheral nerve blocks due to the possibility to localize the nerve through an appropriate motor response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques do not only decrease general anesthesia drawbacks but they also lead to effective analgesia (6)(7)(8). In animals many surgical operations especially in the distal parts of the limbs can be performed under peripheral nerve block such as sciatic and femoral nerves block of the pelvic limbs in cattle, sheep and dogs (9)(10)(11) and brachial plexus nerve block in the forelimbs in cattle, dogs and cats (3,5,7,9).…”
Section: Introductionmentioning
confidence: 99%